2023
DOI: 10.3390/jcm12051865
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Irritable Bowel Syndrome after Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Their Association: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Aim: Investigate the prevalence of irritable bowel syndrome (IBS) after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and assess the association between IBS and SARS-CoV-2 infection. Methods: A systematic literature search for PubMed, Web of Science, Embase, Scopus, and the Cochrane Library was performed to identify all reports published before 31 December 2022. The confidence interval (CI), estimation effect (ES) of prevalence, and risk ratios (RR) were calculated to evaluate the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…The results revealed that the frequency of IBS was 17%, but it only included 4 studies. Two recent systematic reviews and meta-analyses assessing the prevalence of IBS after SARS-CoV-2 infection by Wang et al and Marasco et al included those studies using different diagnostic criteria for IBS such as Rome III criteria and a self-designed questionnaire [46,47]. Our meta-analysis includes only those studies using the latest Rome IV criteria as inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the frequency of IBS was 17%, but it only included 4 studies. Two recent systematic reviews and meta-analyses assessing the prevalence of IBS after SARS-CoV-2 infection by Wang et al and Marasco et al included those studies using different diagnostic criteria for IBS such as Rome III criteria and a self-designed questionnaire [46,47]. Our meta-analysis includes only those studies using the latest Rome IV criteria as inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…and Marasco et al . included those studies using different diagnostic criteria for IBS such as Rome III criteria and a self-designed questionnaire [46,47]. Our meta-analysis includes only those studies using the latest Rome IV criteria as inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 может приводить к возникновению висцеральной гиперчувствительности вследствие развития поствоспалительных изменений слизистой оболочки кишечника и изменений нейрогуморальной регуляции физиологических процессов в ЖКТ [14].…”
unclassified